Poly(ethylene) terephthalate (PET) waste upcycling - Mok, Darrel Sheng Yong (Nanyang Technological University, 2022)
The huge increase in the creation and incineration of post-consumer poly(ethylene terephthalate) (PET) waste have resulted in an urgent need of for efficient recycling processes such as chemical recycling. In this study, the depolymerization of pure and recycled poly(ethylene) terephthalate were carried out in two types of alkaline hydrolysis. The first type of alkaline hydrolysis depolymerized ball milled pure (BMP) PET in a potassium hydroxide (KOH) solution, heated to 160°C using an oven for 60 mins. After the reactions, the residual solids were removed by centrifugation and weighted to form a characterization. The optimal BMP PET to achieve highest PET conversion of 73.4% occurs at KOH concentration of 3.47M and PET concentration of 13.33g/L. The byproducts of this reactions composed of ethylene glycol and terephthalic potassium salt were in liquid phase. They were electrolyzed using electrochemical impedance spectroscopy (EIS) to convert the ethylene glycol into formic acid, which were used to obtain terephthalate acid (TPA). The results of the reaction were analyzed using High Performance Liquid Chromatography (HPLC). The second type of alkaline hydrolysis depolymerized ball-milled or 5 mm flakes recycled PET in potassium or sodium hydroxide solution, heated to 60°C to 80°C for 6 hr. After the reactions, the residual solids were removed by centrifugation and weighted to form a characterization. The byproducts of this reactions composed of ethylene glycol and terephthalic potassium salt or terephthalic sodium salt in liquid phase. The optimal ball-milled recycled colorless (BMRC) PET concentration to achieve highest BMRC PET conversion of 100% in 3M NaOH is 95 g/L and the optimal hand cut recycled green (HCRG) PET concentration to achieve highest HCRG conversion rate of 100% in 9M NaOH is 36 g/L.